Mapeamento de dados para sistema de informação de Pós-graduação - Halicki, Jaqueline Pereira Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The scientific, technological and social development is directly linked to information. It is the guarantee of freedom, enhancing in man his ability of choice, decision for himself and for society. Information Technology and Communication (ICT) are part of that context and subject of investigation by several scholars, particularly with regard to how we relate to these technologies, either as individuals or as organizations. In public institutions, especially the universities, ICT present themselves as challenges and at the same time has enabled significant changes mainly in the planning, organization, representation, preservation, use and dissemination of the knowledge produced in Graduate Programs . Thus, considering the volume of information produced by graduate programs, one arrives at the problem of this research: As the conceptual mapping data can contribute to the structuring of an information system graduate from a higher education institution from its co-existence with the system of CAPES? The institution selected for the survey refers to the Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP), specifically the Dean of Graduate (PROPG) and CAPES – Coordenação de Aperfeiçoamento de Pessoal de Nível Superior. The choice of UNESP is based on the University and in the consolidated position of its Graduate programs and in the experience of the author in the academic follow-up with graduate UNESP and the State University of Rio de Janeiro (UERJ) programs. This research is characterized as bibliographic descriptive and analytical for theoretical and methodological research of the topics discussed, and a quantitative and qualitative approach and action research to the analysis of data collection systems of the UNESP-PROPG and CAPES. The results obtained so far point to the importance of integrating data from graduate as a need for institutions that aim at transparency in its activities and best practices for managing ...

O desenvolvimento científico, tecnológico e social está diretamente associado à informação. Ela representa garantia de liberdade, potencializando no homem sua capacidade de escolha, de decisão para si mesmo e para a sociedade. As Tecnologias da Informação e Comunicação (TIC) fazem parte desse contexto sendo objeto de investigação de vários estudiosos, principalmente no que se refere à forma como nos relacionamos com estas tecnologias, seja como indivíduos ou como organizações. Nas instituições públicas, especificamente nas Universidades, as TIC se apresentam como desafios e ao mesmo tempo tem possibilitado mudanças significativas principalmente, no planejamento, na organização, na representação, na preservação, no uso e na disseminação do conhecimento produzido nos Programas de Pós-graduação. Assim, considerando o volume de informações produzidas pelos programas de pós-graduação, chega-se ao problema desta pesquisa: Como o mapeamento conceitual de dados pode contribuir na estruturação de um sistema de informação da pós-graduação de uma instituição de ensino superior a partir de sua co-existência com o sistema de avaliação da CAPES? As instituições escolhidas para a pesquisa referem-se à Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP), especificamente a Pró-reitoria de Pós-graduação (PROPG) e a CAPES – Coordenação de Aperfeiçoamento de Pessoal de Nível Superior. A escolha pela UNESP fundamenta-se na posição consolidada da universidade em seus programas de pós-graduação e na experiência da autora no acompanhamento acadêmico junto aos programas de pós-graduação da UNESP e da Universidade do Estado do Rio de Janeiro (UERJ). A presente pesquisa caracteriza-se como descritiva bibliográfica e analítica para a investigação teórica e metodológica dos temas abordados, com abordagem quanti-qualitativa e pesquisa-ação, para a análise dos sistemas de ...
Keywords: Sistemas de coleta automatica de dados; Tecnologia da informação; Ensino superior